Immobilization of graphene-derived materials at gold surfaces: Towards a rational design of protein-based platforms for electrochemical and plasmonic applications. (1st January 2018) - Primo, Emiliano N.; Bollo, Soledad; Rubianes, María D.; Rivas, Gustavo A.
Abstract: This work is focused on the critical analysis of the non-covalent modification of a thiolated-gold surface with different grapheneous materials and the covalent attachment of bovine serum albumin (BSA) as a model protein. The main goal was to find a relationship between the nature and amount of the grapheneous nanomaterial, the amount of immobilized protein, and the electrochemical and plasmonic properties of the resulting platforms. The characterization of the grapheneous nanomaterials (graphene oxide (GO), GO modified with chitosan (CHIT), (GO-CHIT), and chemically reduced GO-CHIT (RGO-CHIT)) was performed by using FTIR, Raman, TGA, Dynamic light scattering (DLS), UV–Vis spectroscopy and ζ-potential measurements. The characterization of the thiolated-gold surfaces modified with the different nanomaterials and BSA was performed using surface plasmon resonance (SPR), cyclic voltammetry, electrochemical impedance spectroscopy (EIS) and scanning electrochemical microscopy (SECM). The pH of the grapheneous materials dispersions demonstrated to be a critical parameter to control the assembly of the nanomaterials and the model protein at the gold surfaces and, consequently, the electroactivity and plasmonics of the resulting platforms. When using GO, the optimum pH is 8.00 while in the case of GO-CHIT and RGO-CHIT, pHs << pKa, CHIT are the most adequate. We demonstrated that in the case of our model system, if the detection method depends on the direct quantification of the amount of BSA immobilized at the platform (like SPR), the use of GO is the best option; while if the detection mode depends on the changes in the electrochemical response of a redox marker (like EIS), the selected grapheneous material should be RGO. Graphical abstract: Highlights: GO, chitosan-modified GO (GO-CHIT) and reduced GO-CHIT (RGO-CHIT) were non-covalently assembled at Au surfaces. A rational analysis for the selection of the graphene-derived materials and their immobilization conditions was performed. The assembly of GO, GO-CHIT and RGO-CHIT and protein loading is conditioned by the pH of the nanomaterials dispersion. GO is the best option when transduction depends on the amount of protein immobilized at the platform (like SPR). RGO is the best option when transduction relies on the indirect change in the response of a redox marker (like EIS).